Augmented Reality Flashcards for Enhancing Science Literacy and Academic Therapy in Mangrove Ecosystem Learning: A Participatory Action Research Study (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This community service initiative responds to low science literacy among coastal students, specifically on mangrove ecosystems, due to a lack of contextual learning media. Using a Participatory Action Research (PAR) approach over 10 weeks with teachers and students at MA Raudhatul Islamiyah Pembengis, West Tanjung Jabung, this study developed and tested the effectiveness of Augmented Reality (AR) Flashcards. Academic therapy, here referring to targeted pedagogical interventions to reduce learning barriers and enhance cognitive engagement, was integrated into the process. Results show a significant improvement in science literacy, with a 65% increase in conceptual understanding and a 58% rise in analytical skills. The program also enhanced teachers’ competence in creating innovative media and established a sustainable practitioner community. The integration of PAR with AR technology proves to be an effective, innovative strategy for advancing science literacy and academic support in coastal areas. This approach demonstrates strong potential for replication in other coastal and resource-limited educational contexts.